2010
DOI: 10.1007/s10832-010-9608-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of calcining temperature on the properties of 0-3 piezoelectric composites of PZT and a liquid crystalline thermosetting polymer

Abstract: We report on the optimisation of a recently developed high performance 0-3 piezoelectric composite comprising of the piezoelectric Lead Zirconate Titanate (PZT) powder and a liquid crystalline thermosetting matrix polymer (LCT). The matrix polymer is a liquid crystalline polymer comprising of an HBA-HNA backbone with phenylethynyl end-groups. The use of a high performance polymer makes the composite a possible candidate to be used in sensor applications at elevated temperatures. The composite properties were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The effect of calcination temperature on the piezoelectric properties of PZT 5A4 powder was previously investigated, and it has been reported that further calcinations of commercially available PZT powder improve the compositional homogeneity and thereby the piezoelectric properties. 27,30 From Fig. 1, it is clear that the crystallinity increases for the powder calcined at 1200°C compared to the as-received PZT powder, which will lead to better piezoelectric properties.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of calcination temperature on the piezoelectric properties of PZT 5A4 powder was previously investigated, and it has been reported that further calcinations of commercially available PZT powder improve the compositional homogeneity and thereby the piezoelectric properties. 27,30 From Fig. 1, it is clear that the crystallinity increases for the powder calcined at 1200°C compared to the as-received PZT powder, which will lead to better piezoelectric properties.…”
Section: Resultsmentioning
confidence: 99%
“…The particle size measured with SEM is about 3-5 µm, which is in good agreement particle size measured by laser scattering. The phase purity and compositional homogeneity are studied by x-ray powder diffraction using a Bruker-AXS D5005 diffractometer [11,15]. The calcined powder crystallizes in a perovskite structure with the coexistence of rhombohedral and tetragonal phases.…”
Section: Methodsmentioning
confidence: 99%
“…The 0-3 composites are considered to be the least complicated in terms of manufacturing and ease of molding in complex, predesigned shapes. Although there have been many reports about piezoelectric-polymer composites with 0-3 connectivity, only a handful of investigations have been carried out on the effect of poling conditions on the piezoelectric properties of the composites for polymer matrices with different electrical conductivities [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve its piezoelectric properties the as-received powder was calcined at 1200 C for 2 h in a closed alumina crucible in a Nabertherm furnace applying a heating rate of 5 C/min. The calcined powder was ball milled using yttria stabilized zirconia balls of 5 mm diameter in cyclohexane for 4 hrs [10]. Subsequently, the powder was dried at 150 C and stored in a closed container to avoid moisture absorption.…”
Section: Methodsmentioning
confidence: 99%